Sistem Pendukung Keputusan Penentuan Calon Penerima Bantuan Sosial Rumah Tidak Layak Huni (RTLH) Menggunakan Metode Simple Additive Weighting (Saw) (Studi Kasus : Kelurahan Semarang, Kabupaten Banjarnegara) - Meliana Dwi Saputri; Khalimaturofi’ah .; Lutfi Nur Azizah (Journal Of Informatics And Busisnes, 2025)
The issue of Uninhabitable Housing (RTLH) represents a significant social problem that directly relates to the fulfillment of basic human needs for adequate shelter. The accuracy in determining prospective beneficiaries of RTLH social assistance is crucial to ensure fairness and effectiveness in government aid distribution. However, the selection process has often been conducted manually and subjectively, leading to inefficiency and potential bias in decision-making. This study aims to design and implement a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to enhance objectivity, transparency, and efficiency in the decision-making process for RTLH assistance beneficiaries. The system was developed using the Waterfall software development model, consisting of requirement analysis, system design, implementation, and testing phases. Evaluation was conducted through Black Box Testing and a Likert-scale questionnaire distributed to five village staff respondents. The results indicate that the system performs effectively with no detected functional errors and achieved an eligibility score of 92.4% (very good category). Hence, the developed system is feasible and effective in assisting village officials in objectively and transparently determining prospective RTLH social assistance recipients.